The center of the incisive papilla for the selection of complete denture maxillary anterior teeth in 4 racial groups - Nogueira, Sergio Sualdini [UNESP]; Arioli Filho, João Neudenir [UNESP]; Varjão, Fabiana Mansur (Quintessence Publishing Co Inc, 2008)
Objectives: To evaluate the use of the center of the incisive papilla as a guide for the selection of the proper width of maxillary dentures in 4 racial groups. Method and Materials: One hundred sixty stone casts were obtained from impressions of the maxillary arch of white, black, mixed, and Asian subjects. The occlusal surfaces of the casts were photocopied and the images placed on a digitizer. The most anterior and posterior points of the papilla and cusp tips of the canines were digitized. Dentofacial Planner Plus software was used to calculate the distance from a line passing through the cusp tips of the canines to the center of the papilla, defined as the midpoint of the anterior and posterior points of the papilla. The selection error (in millimeters) due to the clinical application of the method of the incisive papilla was calculated and analyzed. Results: In all studied racial groups, there was no coincidence between the center of the incisive papilla and the canine line. The utilization of the center of the papilla would lead to the selection of wider artificial teeth. In 24.9% of the white, 19.3% of the mixed, 32.9% of the black, and 15.5% of the Asian populations, errors greater than 4 mm would be present with the utilization of the papilla. Conclusion: The method of the center of the incisive papilla is not accurate, but may aid in initial artificial teeth selection for the racial groups studied. (Quintessence Int 2008;39:841-845)
Keywords: Artificial teeth; Complete denture; Dental esthetics; Race